2007
DOI: 10.1002/dir.20075
|View full text |Cite
|
Sign up to set email alerts
|

Giving an “e-human touch” to e-tailing: The moderating roles of static information quantity and consumption motive in the effectiveness of an anthropomorphic information agent

Abstract: This study examines the impact of having an anthropomorphic information agent (a humanlike chatbot that acts as an interactive online information provider) in an online store on consumers’ attitude toward the Web site, product, and their purchase intentions. Using consumer experiments, we show that the impact of the anthropomorphic information agent is moderated by the amount of static product information available on the Web site and the consumer's consumption motive at the time of visiting the Web site. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 42 publications
2
51
0
10
Order By: Relevance
“…Echoing Goodwin and Ross (1992), the level of inequity is positively associated a task-related orientation to resolve it. In line with previous research (Shiv and Fedorikhin, 1999;Isbell and Wyer, 1999;Sivaramakrishnan et al, 2007) this task-related or utilitarian orientation is positively with information processing along the central route.…”
Section: Intensity Of Dissatisfaction and Consumption Valuesupporting
confidence: 91%
See 2 more Smart Citations
“…Echoing Goodwin and Ross (1992), the level of inequity is positively associated a task-related orientation to resolve it. In line with previous research (Shiv and Fedorikhin, 1999;Isbell and Wyer, 1999;Sivaramakrishnan et al, 2007) this task-related or utilitarian orientation is positively with information processing along the central route.…”
Section: Intensity Of Dissatisfaction and Consumption Valuesupporting
confidence: 91%
“…In line with novelty seekers' emphasis on entertainment and emotional attraction, we assume that with regard to online complaining a hedonic consumption value applies (Rodgers et al, 2005). Thus, in line with Sivaramakrishnan et al, 2007) inherent novelty seekers follow a peripheral route in their attitude development towards online complaining.…”
Section: Inherent Novelty Seeking and Consumption Value Novelty Seekementioning
confidence: 99%
See 1 more Smart Citation
“…For example, Holzwarth, Janiszewski, and Neumann (2006) found that the perception of social presence generated by an avatar on a shopping website leads to a more positive brand attitude, higher satisfaction with the retailer, and greater shopping intention. Prior research has suggested that social presence is also enhanced by anthropomorphic agents, such as virtual salespeople (e.g., Nowak and Biocca 2003;Sivaramakrishnan, Wan, and Tang 2007). Consumers experience a greater social presence when they perceive an avatar as a digital representation of another human being than as a computer-controlled agent (Guadagno et al 2007).…”
Section: Social Presencementioning
confidence: 98%
“…6,9 Interactive marketers are increasingly leveraging avatars as sophisticated artificial intelligence programs that interact with consumers in real time. 12,13 Avatars can be employed as a useful apparatus for promoting e-health marketing. [14][15][16][17] In the e-health domain, virtual avatars are e-health advisors, [14][15][16][17][18] web-based healthcare agents, 19 medical document readers for patients with low health literacy, 20 and more.…”
Section: E-health Marketing In Three-dimensional Virtual Worldsmentioning
confidence: 99%